IFP-Intuitionistic Fuzzy Soft h-Ideals of Hemirings and Its Decision Making - Qi Liu; Jianming Zhan (Journal of Applied Mathematics)
The aim of this paper is to introduce the concepts of IFP-intuitionistic fuzzy soft h-ideals and IFP-equivalent intuitionistic fuzzy soft h-ideals of hemirings. Some characterizations and properties of them are given. In particular, some good examples are explored. Finally, we investigate aggregate intuitionistic fuzzy h-ideals of hemirings based on decision making.